Comparative evaluation of the blends of gas-to-liquid (GTL) fuels and biodiesels with diesel at high idling conditions: an in-depth analysis on engine performance and environment pollutants - Hossain, S.; Masjuki, Haji Hassan; Varman, Mahendra; Kalam, M.A.; Rahman, S.M.A. (Royal Society of Chemistry, 2015)
This study focuses on the physicochemical fuel characteristics and engine performance-emission features of three prospective alternative transportation fuels: Alexandrian laurel biodiesel (ALBD), jatropha biodiesel (JBD) and GTL fuel at high idling conditions. The blends of GTL fuel (G10, G20), JBD (J10, J20) and ALBD (AL10, AL20) with diesel had been investigated in a multi-cylinder diesel engine at different load-speed conditions. Analysis of the fuel properties showed a linear variation of the major fuel properties with an increase of alternative fuel quantity in the blends. Engine performance test results revealed an average decrease of brake specific fuel consumption (BSFC) (ca. 8.65-12.26) and brake specific energy consumption (BSEC) (ca. 8.27-11.51), but a higher brake thermal efficiency (BTE) (ca. 8.56-12.58) by GTL blends, whereas, the biodiesel blends showed higher BSFC (ca. 5.01-12.18) and BSEC (ca. 3.41-9.67) and lower BTE (ca. 3.68-9.93), respectively, than those of diesel. Referring to the emission analysis, the results revealed that GTL blends showed a slight reduction in NOx (ca. 3.89-6.85), but a significant reduction in CO (ca. 48.25-51.38), HC (ca. 44.81-51.43) and smoke (ca. 15.21-18.78), respectively, when compared to diesel. The biodiesel blends demonstrated reduced CO (on average ca. 29.12-33.71), HC (ca. 29.67-35.46) and smoke (ca. 2.49-6.87), but increased NOx (on average ca. 2.83-9.81), respectively, than those of diesel.